Factors Related To The Actions Of Midwives In Providing Antenatal Care - Putra Apriadi Siregar (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: Midwives' actions under service standards are useful in applying the norms and performance levels needed to achieve the desired results. Midwives in providing antenatal care will have a significant impact on antenatal care services Methods: This study used a cross-sectional design. This study's population was 41 midwives who worked in the District of Kota Pinang, Labuhanbatu Selatan Regency (total sampling). The instrument used was a questionnaire about age, education, knowledge, attitudes, and midwives' actions in providing antenatal care. The bivariate analysis used exact fisher test and prevalent rate (PR). Results: The exact fisher test results showed that the midwife's age (p = 0.192), education (p = 0.175), knowledge (p = 0.390) (PR = 2.311) were not related to the midwife's actions in antenatal care. The variable of midwife attitudes (p = 0.018) (PR = 5,500) was related to the actions of midwives in antenatal care. Conclusion: A midwife who has a good attitude has a risk taking good actions than a midwife who has a bad attitude. It is hoped that the South Labuhanbatu Health Office will be more active in improving the skills of midwives in providing antenatal services with training on antenatal care..